The structure of western Serra do Curral, Quadrilátero Ferrífero, and tectonic control of the high-grade iron hard bodies - Sanglard, J.; Rosiere, C.; Santos, J.; McNaughton, Neal; Fletcher, Ian (Universidade de Sao Paulo, 2014)
The structure of western Serra do Curral, Quadrilátero Ferrífero, represents the partial exposure of a syncline that verges to NNW - Piedade Syncline. This regional structure has parasitic folds denominated as B1A which are refolded by folds B1B that also have vergence to NNW. Both of them have ENE-WSW direction, are non-cylindrical folds and configure an interference pattern that is similar to Type 3 from Ramsay. This refolding occur during progressive deformation. The occurrence of highgrade magnetitic-martitic accumulation (> 64% Fe) of medium size (~ 100 Mt) is controlled by the combination of these folds and high angle thrust fault, both with the same direction. Above these structures, there is a development of folds with NNWSSE direction and WSW vergence (B2 folds). These folds are restricted to the B1 limbs and they configure an interference pattern named "abbuting fold". The age obtained by U/Pb SHRIMP on monazite grains is 2034 ± 11 Ma. The monazite grains occur on textural balance with the iron oxide from high-grade accumulations. This age corresponds to the formation timing of the high-grade bodies and suggests that the mineralization process is contemporary to the regional metamorphic peak of Quadrilátero Ferrífero.